Noise mapping due to motor vehicle activities in the by-pass ring road area of the city of Kendari - Irwan Lakawa; Syamsuddin; Hujiyanto; Vickky A. Ilham (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2023)
The By-Pass Ring Road in Kendari serves as a crucial artery, facilitating accessibility and mobility between the city center and burgeoning outskirts. However, heightened traffic has led to a notable upswing in noise along the highway. This study aims to systematically map the distribution of this noise across various land uses in the vicinity. The findings reveal a vehicular composition predominantly comprised of motorcycles (68%), followed by light vehicles (27%), and heavy vehicles (5%). Notably, although heavy vehicles constitute a mere 5%, they significantly influence the elevation of noise levels. The highest noise intensity impacting land use is observed in service areas, succeeded by commercial and school zones, with the lowest levels recorded in settlement areas. The mapped results depict a noise exposure of 67 dB reaching receptors, coupled with an average noise reduction of 9 dB. Remarkably, as the average distance from the noise source on the highway to the receptors increases (averaging 14 meters), there is a discernible reduction in noise intensity. This visually apparent trend is corroborated by the noise mapping results.